Impact of Goat Manure, Dolomite, Zeolite, and Decomposer Trichoderma sp. Amendments on the Chemical Characteristics of Inceptisol, Growth and Production of Shallot - M Nur Faiz Septiawan; Rossyda Priyadarshini; Moch Arifin (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Inceptisol is a type of young soil with low NPK nutrient content, which affects the yield of shallot. Efforts to improve the fertility of Inceptisol involve the application of soil amendments. The objective of this study to evaluate the most effective amendments for improving the chemical characteristics, enhancing the growth and yield of shallot. The research was conducted at the Tropical Horticulture Study Center (PKHT), IPB University, Bogor. The method used a two-factor Randomized Block Design (RALF). The first factor the type and combination of amendments (P), is P0 (Control), P1 (Dolomite), P2 (Goat Manure), P3 (Dolomite + Goat Manure), P4 (Dolomite + Goat Manure + Zeolite), P5 (Dolomite + Goat Manure + Trichoderma sp.), and P6 (Dolomite + Goat Manure + Zeolite + Trichoderma sp.). The second factor the variety of shallot (J), which included J1 (Tajuk Variety) and J2 (Sakato Variety). The results showed that the application of amendments and decomposers significantly influenced the chemical characteristics of Inceptisol. Treatment P6 (dolomite, goat manure, zeolite, and Trichoderma sp.,) produced the best results compared to other treatments. Meanwhile, the variety of shallot plants did not have a direct impact on the chemical characteristics of Inceptisol. Keywords: Amendments, Chemical characteristics, Decomposer, Inceptisol, Onion.